The Effect of Generative AI-Based Content Quality on Purchase Intention: A Study on TikTok Users - Muhammad Alfito Danuarta; Ratih Amelia (Jurnal Informatika Ekonomi Bisnis, 2026)
This study empirically examines the direct influence of Generative AI and content creation on purchase intention among TikTok users in Indonesia. Grounded in the Stimulus-Organism-Response theory, GenAI and content creation are positioned as digital marketing stimuli that shape consumer behavioral responses. Using a quantitative approach with an explanatory research design, data were collected via an online questionnaire distributed to Generation Z and Millennial users in East Java who had been exposed to AI-assisted promotional content on TikTok. A total of 169 valid respondents were obtained through purposive sampling. Multiple linear regression analysis was employed after confirming validity, reliability, and classical assumption tests. Results indicate that GenAI (β = 0.893, t = 16.673, p < 0.001) and content creation (β = 0.357, t = 5.088, p < 0.001) both significantly and positively influence purchase intention, explaining 78.3% of its variance (Adjusted R² = 0.783). GenAI emerged as the dominant predictor (Beta = 0.737). This study contributes to the digital marketing literature by simultaneously testing two variables previously examined in isolation within the short-video platform context of TikTok.